2016
DOI: 10.1111/add.13591
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol marketing and youth alcohol consumption: a systematic review of longitudinal studies published since 2008

Abstract: Background and Aims Youth alcohol consumption is a major global public health concern. Previous reviews have con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
223
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(239 citation statements)
references
References 36 publications
7
223
1
8
Order By: Relevance
“…When a user posts content related to alcohol they don't just promote alcohol they also generate data that registers their preference for alcohol in specific times, places and cultural contexts. Systematic reviews (Anderson et al 2009;Jernigan et al 2016) of the effects of marketing on alcohol consumption continue to operationalise exposure to a marketing message as per a mass media channel, even where they examine digital marketing material. While platforms are now critical actors in shaping brand activity and user engagement, these reviews neglect, or set aside, the role platforms and their users play in alcohol marketing.…”
Section: A Media Platform Perspective On Alcohol Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…When a user posts content related to alcohol they don't just promote alcohol they also generate data that registers their preference for alcohol in specific times, places and cultural contexts. Systematic reviews (Anderson et al 2009;Jernigan et al 2016) of the effects of marketing on alcohol consumption continue to operationalise exposure to a marketing message as per a mass media channel, even where they examine digital marketing material. While platforms are now critical actors in shaping brand activity and user engagement, these reviews neglect, or set aside, the role platforms and their users play in alcohol marketing.…”
Section: A Media Platform Perspective On Alcohol Marketingmentioning
confidence: 99%
“…Studies of social media have offered taxonomies of brand activities, and determined effects on alcohol consumption, but not yet examined the role that the platforms themselves play in shaping alcohol marketing (Anderson et al 2009; Atkinson et al 2016;Carah et al 2014;Christlow et al 2015De Bruijn et al 2016Jernigan and Rushman 2014;Jernigan et al 2016;Jones et al 2015;Lobstein et al 2016;Mart et al 2009;Meier 2011;Nicholls 2012). Public health researchers need to pay 'critical and analytical attention' to alcohol marketing on media platforms (McCreanor et al 2013;Niland et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2 Systematic reviews of longitudinal research have indicated that exposure to alcohol advertising influences young people's beliefs and attitudes about drinking, and increases the likelihood that adolescents will start to use alcohol or will drink more if they are already using alcohol. 3 Controls on alcohol advertising are recognised as an essential feature of the comprehensive approach required to reduce alcohol-related harm. 1,4,5 In Australia, as in other countries, restrictions on alcohol advertising mainly exist through industry self-regulation 6 , although no evidence exists that self-regulation is effective at curbing alcohol promotion.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol advertising permeates televised high profile sports virtually unrestricted, despite evidence of its influence on youth consumption. 36 Similarly, alcohol continues to become more easily accessible by youth via availability and low prices through the emerging monopoly of the big box liquor outlets (booze barns). 37,38 Federal and State governments and the other authorities that have responsibility to regulate such undesirable influences are well aware of the need for rigorous regulation but continue to take only token actions.…”
mentioning
confidence: 99%
“…37,38 Federal and State governments and the other authorities that have responsibility to regulate such undesirable influences are well aware of the need for rigorous regulation but continue to take only token actions. 36 Sadly, the powerful advertising and alcohol industries (like the fast food and tobacco industries) are purported to continue to wield far too much political power and this stifles appropriate regulation.…”
mentioning
confidence: 99%